The State Defense Effort To Drive The National Small Industries In The Contemporary Global Landscape - Salsabiela, Bilqis Fitria (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract - The basic points in the state defense is reflected by loving our country land, recognize to be one nation and state, believe on Pancasila as the ideology for our country, want to sacrifice for the nation and state and also has an ability to State Defense which’s corellated with the effort to drive the national small industries in this international trade. The key success for a country is come from the human resources which’s ready to face the change, so that increasing the quality of human resources for small local industries is a main key to struggle in this contemporary global landscape. Keywords: Defence The Country, Small Industries, International Trade, Human Resource, Economy.